Movement velocity as a measure of exercise intensity in three lower limb exercises - Conceição, F.; Fernandes, J.; Lewis, M.; Gonzaléz-Badillo, J. J.; Jimenéz-Reyes, P. (Journal of Sports Sciences, 2016)
The purpose of this study was to investigate the relationship between movement velocity and relative load in three lower limbs exercises commonly used to develop strength: leg press, full squat and half squat. The percentage of one repetition maximum (%1RM) has typically been used as the main parameter to control resistance training; however, more recent research has proposed movement velocity as an alternative. Fifteen participants performed a load progression with a range of loads until they reached their 1RM. Maximum instantaneous velocity (Vmax) and mean propulsive velocity (MPV) of the knee extension phase of each exercise were assessed. For all exercises, a strong relationship between Vmax and the %1RM was found: leg press (r2adj = 0.96; 95% CI for slope is [-0.0244, -0.0258], P < 0.0001), full squat (r2adj = 0.94; 95% CI for slope is [-0.0144, -0.0139], P < 0.0001) and half squat (r2adj = 0.97; 95% CI for slope is [-0.0135, -0.00143], P < 0.0001); for MPV, leg press (r2adj = 0.96; 95% CI for slope is [-0.0169, -0.0175], P < 0.0001, full squat (r2adj = 0.95; 95% CI for slope is [-0.0136, -0.0128], P < 0.0001) and half squat (r2adj = 0.96; 95% CI for slope is [-0.0116, 0.0124], P < 0.0001). The 1RM was attained with a MPV and Vmax of 0.21 ± 0.06 m/s and 0.63 ± 0.15 m/s, 0.29 ± 0.05 m/s and 0.89 ± 0.17 m/s, 0.33 ± 0.05 m/s and 0.95 ± 0.13 m/s for leg press, full squat and half squat, respectively. Results indicate that it is possible to determine an exercise-specific %1RM by measuring movement velocity for that exercise.